Orbitofrontal sulcal and gyrus pattern in human: an anatomical study - Thiago Pereira Rodrigues; Mariana Athaniel Silva Rodrigues; Daniel de Araújo Paz; Marcos Devanir Silva da Costa; Ricardo Silva Centeno; Feres Eduardo Chaddad Neto; Sergio Cavalheiro (Arquivos de Neuro-Psiquiatria)
The anatomical characterization of the orbitofrontal cortex in human is limited in literature instead of many functional and clinical studies involving it. Objective Anatomically define the orbitofrontal region aiming to possible neurosurgical treatments and unify the scientific nomenclature as well. Method We analyze eighty four human hemispheres using a surgical microscope. Then we chose four hemispheres and dissect them according to Klinger’ technique. Results We found five main sulcus: olfatory sulcus, orbital medial sulcus, orbital lateral sulcus, orbital transverse sulcus and orbital intermediate sulcus. These sulcus, excluding the intermediate sulcus, delimit five gyrus: rectus gurys, orbital medial gyrus, orbital anterior gyrus, orbital lateral gyrus and orbital posterior gyrus. The main sulcal configuration can be divided on four more frequently patterns. Conclusion Orbitofrontal cortex is associated with many psychiatric disorders. Better anatomical and functional characterization of the orbitofrontal cortex and its connections will improve our knowledge about these diseases.